Pelaksanaan Kegiatan Pojok Taman dalam Meningkatkan Kepedulian Sosial dan Lingkungan di SD Negeri Simaja - Lutfiah Aliyah Rachma Kamojang; Siti Tanisa; Fine Heliyani; Muhammad fadli; Widia Nur Jannah; Muhammad Lutfi (Journal on Education, 2025)
This study examines the implementation of the adiwiyata programme through planting corner activities at SDN Simaja in an effort to shape students' environmental awareness character. Using a descriptive qualitative approach, this study investigates how planting corner activities contribute to fostering environmental awareness. The results showed that the programme succeeded in transforming empty land into a useful green area through students' active involvement in various activities, ranging from land clearing, making vases from plastic waste to plant maintenance. These activities not only improved the aesthetics of the school environment but also developed gardening skills, teamwork and a sense of responsibility in students. Despite challenges such as the lack of focus on the students' difficulty in controlling the commotion, the programme proved to be effective in instilling the values of environmental stewardship. environment. The success of the programme is shown through physical changes in the school environment and increased environmental awareness in students.